Analisis Komprehensif Rencana Pembelajaran Semester (RPS) pada Mata Kuliah Dasar-Dasar Pendidikan, Pendidikan Islam, dan Sejarah Pendidikan Islam dalam Perspektif Outcome-Based Education (OBE) - Ahmad Al Kindi Siregar; Panca Abdini Sitorus; Muhammad Ghozali Maarif; Siti Halimah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to comprehensively analyze the Semester Learning Plans (SLPs) for the courses Fundamentals of Education, Islamic Education, and History of Islamic Education from the perspective of Outcome-Based Education (OBE). The study employs a descriptive qualitative approach using a document analysis design combined with a cross-case analysis of three previously conducted mini-studies. The research data sources consist of the SLPs and the results of the mini-studies for the three courses. The analysis focused on the alignment between Graduate Learning Outcomes (GLOs), Course Learning Outcomes (CLOs), course content, teaching methods, student learning experiences, and the assessment system. The research results indicate that all three course syllabi have met the core components of OBE and demonstrate alignment between learning outcomes, course content, teaching methods, and the assessment methods employed. However, the level of OBE implementation varies across the three courses. The “Fundamentals of Education” course remains oriented toward conceptual mastery; “Islamic Education” emphasizes the integration of Islamic values; while “History of Islamic Education” demonstrates a more optimal implementation of OBE through the use of mini-research projects as a form of authentic learning and assessment. This study concludes that the success of OBE implementation is determined not only by the completeness of the Semester Learning Plan (SLP) components but also by the instructors’ ability to design student-centered, learning-outcome-oriented instruction.